EDUCATION QUALITY ASSURANCE AND COMPARATIVE ACCREDITATION OF SCHOOLS (International Journal of Education and Literature, 2022)
This study aims to determine the quality assurance of education and comparative school accreditation. The method used in this paper is descriptive qualitative and literature study. The results showed that: 1) The measure of the quality of education in schools refers to the degree of excellence of each component, is relative, and always exists in comparison. 2) Steps to improve quality, namely; a) needs analysis, b) vision, mission, and objectives, c) resources for educators and education personnel, d) the process of achieving quality assurance in education, 3) quality management orientation in education, 4) Steps for implementing quality management, namely a) quality planning education, b) implementation of quality-based programs, and c) quality control, and 5) Comparative accreditation of Public Madrasah Aliyah and Private Madrasah Aliyah in Pekanbaru shows that 4 MAN received accreditation A, 2 MAS received accreditation A, 5 MAS obtained accreditation B and 1 MAS obtained C accreditation.